Tissue Culture Studies in Withania somnifera (L.) Dunal - Nara, Haribhau (Plantae Scientia, 2020)
Withania somnifera is an important medicinal herb that has been widely used for the treatment of different clinical conditions. The overall medicinal properties of Withania somnifera make it a viable therapeutic agent for addressing anxiety, cancer, microbial infection, immunomodulation, and neurodegenerative disorders. Biochemical constituents of Withania somnifera like withanolide A, withanolide D, withaferin A and withaniamides play an important role in its pharmacological properties. Proteins like Withania somnifera glycoprotein and lectin like-protein possess potent therapeutic properties like antimicrobial, anti-snake venom poison and antimicrobial. In this review, we have tried to present different pharmacological properties associated with different extract preparations, phytochemical constituents and protein component of Withania somnifera. Future insights in this direction have also been highlighted.